Generic Pipelines Using Docker The DevOps Guide to Building Reusable, Platform Agnostic CI/CD Frameworks - Atkinson, Brandon (Apress, 2018)
Create generic pipelines to reduce your overall DevOps workload and allow your team to deliver faster. This book helps you get up to speed on the pros and cons of generic pipeline methodology, and learn to combine shell scripts and Docker to build generic pipelines. In today's world of micro-services and agile practices, DevOps teams need to move as fast as feature teams. This can be extremely challenging if you're creating multiple pipelines per application or tech stack. What if your feature teams could utilize a generic pipeline that could build, test, and deploy any application, regardless of tech stack? What if that pipeline was also cloud and platform agnostic? Too good to be true? Well think again! Generic Pipelines Using Docker explores the principles and implementations that allow you to do just that. You will learn from real-world examples and reusable code. After reading this book you will have the knowledge to build generic pipelines that any team can use. What You'll Learn: Explore the pros and cons of generic pipeline methodology Combine shell scripts and Docker to build a generic pipeline Implement a pipeline across CI/CD platforms Build a pipeline that lends itself well to both centralized and federated DevOps teams Construct a modular pipeline with components that can be added, removed, or replaced as needed This book is for professionals who use DevOps or are part of a DevOps team, and are seeking ways to streamline their pipelines and drive more deployments while using less code. Brandon Atkinson is a software engineer with more than 14 years of industry experience encompassing analysis, design, development, and implementation of enterprise-level solutions. He is passionate about building teams that scale and enterprise architectures that transforms businesses. He has extensive experience using Azure, AWS, .NET, DevOps, Cloud, JavaScript, Angular, Node.js, and more. Dallas Edwards has more than 10 years of experience as a software engineer. He thrives on creating solutions that are pragmatic, scale easily, and that are easy to test and maintain. His experience encompasses a wide range of expertise, including software development, iOS application development, and DevOps.